Use of Fruits and Infructescense Characters in the Identification of the Acacia Mill. (Leguminosae) Species in Nigeria - Jayeola, A. A.; Folorunso, A. E. (2014)
Fruits and infructescence characters of 31 Acacia Mill, taxa are described in this study. Three species, Acacia auriculiformis A. Cum.ex Benth. A. auricularis A. Cunn. ex. Benth. and A. schweinfurthii Brenan. & Exell., represent new records for Nigeria while three taxa, denoted as Acacia species unidentified A, Acacia species unidentifed B. Acacia unidentified C cannot be determined reliably using the available flora and resources of the herbarium. Mophometric variants were observed in A. gourinaensis A. Chev., A. sieberiana and A. dudgeoni, with the morphs identified temporarily as A. gourinaensis A. Chev. variant a and A. gourinaensis A. Chev. variant c, A sieberiana DC var. villosa A. Chev. variant a and A. dudgeoni Gaib. ex Hall variant a, respectively. What is not known from this study, however, is if the variation is genecological or not. Presence or absence of trichomes on the fruits and peduncle; fissure, vein and constriction patterns all provided stable characters. Migrations arising from nomadic culture may have accounted for the new additions to the flora. A taxonomic key based on the characters of the fruits and infructenscences is included.